Éducation formelle et éducation informelle : regards croisés sur la notion de compétence (transversale) - Vincent Berry; Alain Garcia (Éducation et Socialisation)
This article discusses “Competency-based education” by comparing two research fields: formal and informal education. Firstly, the authors recall the genesis of the notion of (soft) skills and its inclusion into the French school system. The use of this term however shows its limits by the vagueness of its definitions and its areas of application: indeed we see the skills based system collide with the national education system. Finally, the framework of informal education seems to elucidate the problem: here one points out the gap between abstract skills and the real practices that give them meaning.